2022
DOI: 10.1186/s41235-022-00389-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-monotonic developmental trend of holistic processing in visual expertise: the case of Chinese character recognition

Abstract: Holistic processing has been identified as an expertise marker of face and object recognition. By contrast, reduced holistic processing is purportedly an expertise marker in recognising orthographic characters in Chinese. Does holistic processing increase or decrease in expertise development? Is orthographic recognition a domain-specific exception to all other kinds of recognition (e.g. face and objects)? In two studies, we examined the developmental trend of holistic processing in Chinese character recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…The inversion paradigm is easier for children than other paradigms (e.g., composite paradigm) when use Chinese characters as stimuli; and the composite paradigm for Chinese characters was more influenced by writing experiences/performance ( Tso et al, 2014 , 2021 , 2022 ). Consequently, in the present experiments, we choose the inversion effect as a measurable index of perceptual expertise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inversion paradigm is easier for children than other paradigms (e.g., composite paradigm) when use Chinese characters as stimuli; and the composite paradigm for Chinese characters was more influenced by writing experiences/performance ( Tso et al, 2014 , 2021 , 2022 ). Consequently, in the present experiments, we choose the inversion effect as a measurable index of perceptual expertise.…”
Section: Discussionmentioning
confidence: 99%
“…In the inverted images, the relative spatial relations among image elements are turned upside down, and consequently, this slows down the response of the mechanism that is specialized in the spatial configurations of elements in an image (Kao et al, 2010). The inversion paradigm is easier for children than other paradigms (e.g., composite paradigm) when use Chinese characters as stimuli; and the composite paradigm for Chinese characters was more influenced by writing experiences/performance (Tso et al, 2014(Tso et al, , 2021(Tso et al, , 2022. Consequently, in the present experiments, we choose the inversion effect as a measurable index of perceptual expertise.…”
Section: The Developmental Performance Of the Inversion Effect In Chi...mentioning
confidence: 99%
“…Our results are seemingly at odds with findings that HP follows a non‐monotonic U‐shaped function. As has been documented, when children learn Chinese character recognition (Tso et al., 2022), younger, but not older, children perceive a small number of Chinese characters holistically (Tso, Au, & Hsiao, 2014) and attend to all input equally at the onset of reading (Hsiao & Cottrell, 2009). A similar inverted‐U trend has also been proposed to apply in the case of face recognition (Hsiao & Galmar, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…These results suggested that performance in naming words and pseudowords was associated with local but not global processing ability. Similarly, Chinese readers with limited writing experience perceived characters more holistically with longer recognition RT, suggesting the importance of sensitivity to local components for expert reading performance 13,14,15 . Interestingly, higher similarity to the eye movement pattern focusing at the OVP in lexical decision was uniquely predicted by longer RAN RT, suggesting that the ability to accurately xate at the OVP may con ict with the ability to rapidly identify an isolated familiar symbol.…”
Section: Discussionmentioning
confidence: 97%
“…For example, both holistic processing and local featural information are important for face recognition 10,11,12 . Similarly, Chinese character recognition expertise involves an initial increase in holistic perception, followed by enhanced selective attention to local components through writing practice 13,14 , and reading di culties in Chinese are associated with impaired ability to selectively attend to local components 15 . In lexical decision of low frequency Portuguese words, faster response time (RT) was associated with more holistic word perception, suggesting the relationship between word processing e ciency and holistic perception 16 .…”
Section: Introductionmentioning
confidence: 99%